Environmental status of the Gulf of California: A review of responses to climate change and climate variability - Páez-Osuna, F.; Sanchez-Cabeza, J.A.; Ruiz-Fernández, A.C.; Alonso-Rodríguez, R.; Piñón-Gimate, A.; Cardoso-Mohedano, J.G.; Flores-Verdugo, F.J.; Carballo, J.L.; Cisneros-Mata, M.A.; Álvarez-Borrego, S. (Earth-science reviews, 2016)
The Gulf of California (GC) is a unique large marine ecosystem characterized by its rich biodiversity, high biological productivity and endemism of marine life, which are the basis of Mexico's most important fisheries. However, as many other large ecosystems worldwide, it is subject to diverse anthropogenic pressures (overfishing, losses of biodiversity and habitats, pollution, climate variability and climate change (CC)). We reviewed over 180 studies dealing with the impacts of CC and climate variability in the GC region. Main issues on the impact of ENSO events, acidification, sea level rise, and water availability are discussed for the GC in a global context. Impacts of ENSO events on the GC are geographically heterogeneous, upwelling tends to be suppressed, and this in turn influences the distribution and abundance of marine mammals, fishes, shrimps, benthic species, seaweeds and phytoplankton. ENSO events strongly impact small pelagic fishes, key components of the GC ecosystem, thus affecting fisheries in general as well as non-harvested species such as marine mammals and sea birds. Probably the most well-known phenomenon associated to ENSO impact in the GC is coral bleaching, a process by which corals expel most of their microalgal endosymbionts to become pale or white (bleached). Beside shifts in the distributional limits of benthic organisms, invasions of alien species are also occuring. Harmful algal blooms (HABs) are common and recurrent in the GC. Fourteen HAB-forming species have been recorded, with Gymnodinium catenatum being the most frequent. HABs are inhibited by El Niño and promoted by La Niña. During El Niño events the size and biomass of macroalgal blooms tend to decrease. Finally, several aspects that require further research are proposed.